From trauma to growth: A mixed-methods analysis of psychological factors in women’s experiences of temporary marriage - Casmini, Casmini; Musthofa, Musthofa; Saptoni, Saptoni; Anwar, Moh. Khoerul; Abubakar, Lugazo (Psikohumaniora: Jurnal Penelitian Psikologi, 2024)
Temporary marriage is not only about surviving the trauma and crisis but also offers the potential to emerge from difficulties due to its ability to provide meaning from past events. This study aims to measure the level of meaning in the life of female victims of temporary marriage in Singkawang, Indonesia, by exploring their experiences as an optimization to generate positive effects on their lives. Employing a mixed-methods approach that integrates qualitative and quantitative methodologies, the research utilizes an inventory technique to investigate the meanings of life experienced by ten respondents. Additionally, in-depth interviews were conducted with five women who had been impacted by temporary marriage in order to delve into their pursuit of a meaningful life, all of whom consented to the intervention. The findings indicate that women often find themselves as victims of temporary marriage at a middle economic level. The pursuit of a purpose in life emerged as a primary concern, surpassing other factors such as spirituality, self-acceptance, materialism, and problem-solving in the quest for life’s meaning. This situation is often hindered by psychological trauma stemming from challenges encountered within the context of temporary marriage. Through introspection and self-acceptance, individuals embarked on a journey of personal growth, gaining insights and heightened awareness that could serve as a form of intervention through social connection, prayer, close relationships, positive behaviors, experiences, and self-motivation. This research provides an understanding of the fact that difficulties or problems in life can have positive implications by motivating the desire to grow from the temporary marriage experience.